Controlled extrusion-based 3D printing of micro-channels with the geometric modelling of deposited roads. (July 2021) - Haghbin, Naser; Bone, David; Young, Kevin
Abstract: Extrusion-based 3D printing is the most accessible form of 3D printing technology with many applications such as the fabrication of micro-channels. In a controlled extrusion-based 3D printing process, it is of importance to control the 3D printing process using a more reliable road prediction model, which creates micro-features with a minimized size difference in comparison to their original design size. In this study, the sizes of deposited roads were first predicted using three geometric models of rectangle, oblong, and ellipse at different nozzle standoff distances and scan speeds. Then, two computer-aided procedures were developed using these geometric models: the first procedure generated three separate G-code programs for fabricating individual roads; and the second procedure generated three new G-code programs for fabricating micro-channels. It was found that the measured width and height of roads created by the rectangle, oblong, and ellipse models were 17.1 %, 9.7 %, and 22.6 % different than those in the CAD model of roads, respectively, which revealed the oblong model was a better option for controlled 3D printing of individual roads. It was hypothesized that the deviation between the CAD models and measured ones was due to the back-pressure effect and compressive forces caused by the nozzle tip. Moreover, the measured widths and depths of micro-channels created by the rectangle, oblong, and ellipse models had 8.0 %, 6.8 %, and 12 % difference with those in the CAD model, respectively, which indicated the oblong model was relatively a better choice for controlled 3D printing of micro-channels.